ChemInform Abstract: Catalytic Synthesis of N‐Unprotected Piperazines, Morpholines, and Thiomorpholines from Aldehydes and SnAP Reagents. Issue 4 (January 2016) - Luescher, Michael U.; Bode, Jeffrey W.
Abstract: Ring closure of various aliphatic and (hetero)aromatic aldehydes with stannyl amine substrates under slightly differentiated conditions renders possible the access to a broad spectrum of the title compounds.